The Relationship Between Patients’ Sociodemographic Factors And The Selection Of Prosthetic Rehabilitation Treatment - Karina Mundiratri; Nadia Kartikasari; Imam Safari Azhar; Fionna Adhelia Putri; Floreant Indira Naila (Jurnal Medali, 2026)
Background: The success of prosthodontic rehabilitation can be achieved by paying close attention to both subjective and objective examination. Patients’ preferences for the type of prosthesis are also influenced by sociodemographic factors. Sociodemography refers to the background characteristics of each individual. The purpose of this study was to investigate the association between sociodemographic factors including age, gender, occupation and location of residence that may influence the selection of prosthesis type. Method: Cross-sectional study utilized a non-probability sampling method with total of 52 patients who met the inclusion and exclusion criteria, and required partial denture prosthodontic rehabilitation. Data of patiens were collected from the Universitas Airlangga Dental Hospital from 2019 - 2025.Result: Among all study participants, majority of study participants were female and chose fixed partial denture. Sociodemographic factor influencing treatment selection included gender (p = 0.015) and edentulous site (p = 0.034), both of which showed a statistically significant association with the overall patient choice.Conclusion:  gender and edentulous site of the ridge were significantly correlated as factors affecting the prosthesis choice of the patients.